Can a single short-term mechanism account for priming of pop-out?. (October 2015) - Kruijne, Wouter; Brascamp, Jan W.; Kristjánsson, Árni; Meeter, Martijn
Highlights: Priming of pop-out is a short-term phenomenon and decays in 5–8 trials. This also holds after prolonged sequences repeating one target color. This contradicts earlier reports with the same paradigm. The results agree with a previously reported mathematical model of priming. Abstract: Trial-to-trial feature repetition speeds response times in pop-out visual search tasks. These priming effects are often ascribed to a short-term memory system. Recently, however, it has been reported that a 'build-up' sequence of repetitions could facilitate responses over 16 trials later – well beyond twice the typically reported time course (Vision Research, 2011, 51, 1972–1978). Here, we first report two replication attempts that yielded little to no support for such long-term priming of pop-out. The results instead fell in line with the predictions of a previously proposed computational model that describes priming as short-lived facilitation that decays over approximately eight trials (Vision Research, 2010, 50, 2110–2115). In the second part of this study, we show that these data are consistent with a simple formulation of decay with a single timescale, and that there is no significant priming beyond eight trials.